482 Developing a person-centred deprescribing process in primary care for older people living with frailty. (13th April 2023) - Breen, L; Benn, J; Marques, I; Peat, G; Fylan, B; Silcock, J; Mehdizadeh, D; Petty, D; Daffu-O'Reilly, A; Butt, N; Alldred, D P
Abstract: Introduction: Problematic polypharmacy in older people living with frailty can cause harm due to adverse drug events and deprescribing (withdrawing inappropriate medication to manage polypharmacy and improve outcomes (1)) is one solution to mitigate this. Structured Medication Reviews (SMRs) have been commissioned in England to be conducted by Primary Care Network (PCN) pharmacists for which older people living with frailty are a priority group. SMRs are an ideal opportunity to deprescribe for this high-risk population and a person-centred approach is required to ensure deprescribing is safe, effective and acceptable to patients. However, the optimal deprescribing process has not been developed and tested in this context. Aim: To develop a person-centred process for deprescribing for older people living with frailty which could potentially be implemented within SMRs in primary care. Methods: We conducted qualitative research with older people living with frailty, carers and primary healthcare professionals to identify barriers and facilitators to deprescribing in this context in the North of England (2). We then used these findings and a "trigger film" of patients' experiences to conduct Experience-based Co-design (EBCD), a multi-event process where older people living with frailty, informal carers and primary healthcare professionals came together to determine the key features of an ideal deprescribing process and identify priorities for a complex intervention to support the process. Following this, we presented the process model for feedback at the training day of a large multi-site primary care practice based (involving pharmacists, GPs and administrative practice staff) in the North of England and subsequently refined the model to integrate within their evolving SMR programme. Results: The co-designed deprescribing process consisted of 3 phases: 1. Prior to the SMR consultation which involved case-finding of high-risk patients, case-note review for deprescribing eligibility and clinician planning for the consultation, inviting and preparing the patient for the consultation with written information (including what to expect during the medication review, and questions for patients about their medicines to reflect upon); 2. The consultation which included shared decision-making, agreement of plans to stop medicines, recording of decisions in the electronic health record, providing written information for patients on how to safely stop their medicines, safety netting and signposting to post-deprescribing support; 3. Post-consultation which involved evaluating patient experiences and organising follow-up and further review as needed. Key elements of the optimal process to ensure it was person-centred, were effective written and verbal communication for patients (during the entire process), shared decision-making and tailored support post-consultation. Conclusion: We have developed a person-centred process for deprescribing for older people living with frailty and adapted it for implementation within nationally commissioned SMRs in England. Although the model is grounded in the requirements of multiple stakeholders, the final version requires evaluation. The next steps are to design and develop tools which can support our deprescribing process and to undertake feasibility testing in primary care. References: 1. Reeve E, Gnjidic D, Long J, Hilmer S. A systematic review of the emerging definition of 'deprescribing' with network analysis: implications for future research and clinical practice. Br J Clin Pharmacol. 2015;80(6):1254-1268. 2. Peat G, Fylan B, Marques I, Raynor DK, Breen L, Olaniyan J, Alldred DP. Barriers and enablers of successful deprescribing as described by older patients with frailty, supporting peers and clinicians: A qualitative interview study. BMJ Open 2022. 12:e054279.